Protection of Constitutional Rights To A Good And Healthy Living Environment Through Post-Mining Fund Management In Bankruptcy Conditions: An Analysis Of State Authority In The PT Kobatin Case - Sudirman; Abdul Rasyid Saliman; Enny Agustina (Dinasti Research, 2026)
When a mining firm declares bankruptcy, it poses a grave danger to the right to a decent and healthy environment, as stated in Article 28H paragraph (1) of the 1945 Constitution. Using the pari passu pro rata parte basis to pay off creditors, the PT Kobatin case revealed a serious lack of environmental protection by diverting cash meant for reclamation and post-mining guarantees into the bankruptcy estate. In light of the state's constitutional duty to maintain high standards of environmental protection even in the face of bankruptcy, this research seeks to both examine that power and provide a legal interpretation that brings bankruptcy law into harmony with those standards. By reviewing statutes, regulations, judicial rulings, and constitutional law theory, this study employs a case-based normative juridical research methodology. The research findings show that the commercial court placed reclamation funds as bankruptcy assets without considering the human rights dimension and the state's constitutional obligations, creating a false hierarchy of interests between the economic interests of creditors and the constitutional rights of citizens. The implications of this research urge legal reform to establish environmental guarantee funds as trust funds separate from bankrupt estates, strengthen state authority through state's parens patriae in bankruptcy cases involving environmental interests, and establish an environmental priority creditor mechanism that places environmental restoration obligations above the interests of commercial creditors in order to ensure the sustainability of the constitutional rights of future generations.